METAMORPHIC ANALYSIS IN SONG LYRICS BATAK TOBA “JUJUNG GOARHI AMANG” (STUDY OF PORTRAY OF PARENTS) - Marudut Bernadtua Simanjuntak; Zuriyati Zuriyati; Ninuk Lustyantie (PROJECT (Professional Journal of English Education), 2022)
This study aims to analyze the metamorphic sentences contained in popular folk songs in Indonesia. "Jujung Goar Hi Amang" is a Batak Toba literary song that is popular especially among the Batak community. This tune has been extensively performed each at large-scale live shows, famous film soundtracks, and the range of views that exceed four hundred thousand perspectives at the YouTube channel. The meaning of metamorphic sentences in this track includes Toba Batak's cultural values that are represented in metamorphic sentences which whilst analyzed have a totally deep that means, both in phrases of translation that means, cultural tradition, and moral messages. The lyrics of this tune have been created in accordance with emotional expressions that even constitute the life of Batak mother and father who are liable for their children in popular. Keywords:  Metamorphic Analysis, Batak Toba,  Portray of  Parents, Literary Studies